2020
DOI: 10.1002/pbc.28620
|View full text |Cite
|
Sign up to set email alerts
|

Extremely high birth prevalence of sickle cell disease in rural Tanzania

Abstract: Background/objectives: Sickle cell disease (SCD) is an important, hidden cause of childhood mortality worldwide. It is most prevalent in sub-Saharan Africa where national newborn screening programs remain unavailable and most children in rural areas are never diagnosed. We conducted a study at a rural district hospital in northern Tanzania to determine the birth prevalence and community awareness of SCD and to determine the feasibility of using point-of-care testing to enroll newborns in a new SCD clinic for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Similar studies which used HemoTypeSC as the primary screening method in some parts of Africa had sickle cell disease prevalence ranging from 1.1 to 3.9%, with the prevalence of sickle cell trait of 20.6 to as high as 31.6% (26, 43,44). In these studies con rmatory test were laboratory based and they showed a high sensitivity of HemoType SC, point of care test.…”
Section: Discussionmentioning
confidence: 80%
“…Similar studies which used HemoTypeSC as the primary screening method in some parts of Africa had sickle cell disease prevalence ranging from 1.1 to 3.9%, with the prevalence of sickle cell trait of 20.6 to as high as 31.6% (26, 43,44). In these studies con rmatory test were laboratory based and they showed a high sensitivity of HemoType SC, point of care test.…”
Section: Discussionmentioning
confidence: 80%
“…Similar studies that used HemoTypeSC as the primary screening method in some parts of Africa reported sickle cell disease incidences ranging from 1.1 to 3.9%, with a prevalence of sickle cell traits ranging from 20.6 to as high as 31.6% [27,50,51]. In these studies, laboratorybased confirmatory tests were performed, and Hemo-Type SC, a point-of-care test, was highly sensitive.…”
Section: Discussionmentioning
confidence: 87%
“…High prevalence results (SCD ~4%) were also obtained at a hospital in Shirati (rural northern Tanzania) in a separate study undertaken from February to September 2019. In addition to birth prevalence data, this study also demonstrated the value of POC testing (HemoTypeSC TM ) and the need to improve community awareness [ 1575 ].…”
Section: Resultsmentioning
confidence: 96%